2018
DOI: 10.1007/s12209-018-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Mechanism of Erythromycin Ethylsuccinate During Crystallization

Abstract: In this paper, the gelation mechanism of erythromycin ethylsuccinate (EES) during crystallization is investigated for the first time. The generated semisolid gel-like phase exhibited a 3D fibrillar network morphology and the typical rheological properties of gels. The fibers inside the gel-like phase were confirmed to be new types of EES solvates using powder X-ray diffraction, thermogravimetric analysis/differential scanning calorimetry, and gas chromatography. The gelation and crystallization regions in EES-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Additionally, gelation phenomenon cannot happen in all solvents; choosing the suitable solvents can prevent or promote this phenomenon in practical production [14]. Under the gel temperature, several parameters, such as Hansen solubility parameters, Kamlet-Taft parameters, and Hildebrandt solubility parameters [15][16][17], can be introduced to characterize the solvent properties and indicate the gelation tendency of a gelator.…”
Section: Mechanism Of the Gel-crystal Transitionmentioning
confidence: 99%
“…Additionally, gelation phenomenon cannot happen in all solvents; choosing the suitable solvents can prevent or promote this phenomenon in practical production [14]. Under the gel temperature, several parameters, such as Hansen solubility parameters, Kamlet-Taft parameters, and Hildebrandt solubility parameters [15][16][17], can be introduced to characterize the solvent properties and indicate the gelation tendency of a gelator.…”
Section: Mechanism Of the Gel-crystal Transitionmentioning
confidence: 99%
“…It is found that the gelation phenomenon often occurs in the crystallization process of tilmicosin phosphate, which leads to small particle sizes and easy aggregation. In recent years, there have been reports on the gelation phenomenon and gelation mechanism in the process of drug crystallization. Ouyang et al studied the gel formation and spontaneous crystallization of Valnemulin hydrogen tartrate in a mixed solvent system. The results showed that the gel was formed temporarily and played an intermediate role in the amorphous transformation process.…”
Section: Introductionmentioning
confidence: 99%
“…There are a lot of studies that aim to solve the gelation phenomenon during a crystallization process. , Controlling the solution concentration and associated temperature is a common method to optimize the process to avoid gelation. ,, And another method is seeding-assisted crystallization to initialize the nucleation to avoid gel phase formation. It can induce the crystallization process, and the crystal growing from the crystal nucleus can achieve product consistency, to improve the yield and quality of crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al 24 Strong polar interactions between solvent molecules and carboxyl, amine, or acyl groups exposed on the surface of CTX crystals are key factors in forming gels. Su et al 25 studied the gelation mechanism of erythromycin ethylsuccinate (EES) in the crystallization process, and the results indicated that the fibers in the gelatinous phase were new EES solvates. It was concluded that, through intermolecular hydrogen bonds, EES and solvent molecules, through crystallography mismatch, nucleate growth and assemble into fibers.…”
Section: Introductionmentioning
confidence: 99%